The development of circular economy teaching in business: a bibliometric analysis (1994-2022) / Inaya Sari Melati ... [et al.] - Melati, Inaya Sari; -, Wahjoedi; Mukhlis, Imam; Wahyono, Hari (Universiti Teknologi MARA, 2023)
This study aimed to evaluate the development of research on CE teaching in higher education institutions through systematic mapping of scientific literature. This study used a bibliometric approach to map research literatures on CE teaching in higher education using Scopus extracted metadata. The investigation yielded 232 publications, including articles (124), conference papers (59), book chapters (14), conference reviews (13), books (7), editorials (2) and short survey (1). The major findings are: (1) research on CE teaching emerged in 1994; (2) there is a quite limited number of authors, institutions, and countries that produced research in this field; (3) research collaboration is not established significantly; (4) two journals stand out in this field are Sustainability and Journal of Cleaner Production; and (5) general themes of current articles include learning activities, classroom management, higher education, technical aspects, learning output and product design. The findings will be valuable for readers to define the role model in writing about CE teaching in business, identify potential collaboration with authors and institutions across countries, and develop new issues on CE teaching in the existing areas of research or, otherwise, develop the existing issues in new areas of research. Practically, this study provides a comprehensive and relevant review of the literatures on CE teaching that can be used to teachers, lecturers, and education policy makers to determine the better framework to introduce Circular Economy for business students gradually and continuously.